2012
DOI: 10.1044/0161-1461(2012/10-0083)
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Literacy in Children With Autism: An Exploration of Developmental and Contextual Dynamic Processes

Abstract: Profiles were associated with language and were illustrated by heterogeneity with potentially unequal achievements between code- and meaning-based skills. Implications for speech-language pathologists and other educators are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
74
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 37 publications
14
74
0
2
Order By: Relevance
“…These findings are consistent with previous studies showing particular strengths in print-related emergent literacy skills, such as letter identification, in young children with autism [26] and imply that these skills may not be directly a result of parent teaching. Our results also showed that parents of children with autism were more likely to point out signs/words in the environment, even after correcting for age, which suggests that parents may be sensitive to their children’s strengths and focus of attention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous studies showing particular strengths in print-related emergent literacy skills, such as letter identification, in young children with autism [26] and imply that these skills may not be directly a result of parent teaching. Our results also showed that parents of children with autism were more likely to point out signs/words in the environment, even after correcting for age, which suggests that parents may be sensitive to their children’s strengths and focus of attention.…”
Section: Discussionsupporting
confidence: 92%
“…Data on the home literacy environment in the current study were gathered via parent report rather than direct assessment. Although previous research has found good correlations between parent report and children’s print-related literacy skills [26, 49], nonetheless, there is potential for bias towards responses perceived to be more favourable. SES has been shown to impact home literacy environments and literacy behaviours [46, 52]; however, SES was not explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also support the findings of other studies of preschool children with ASD that the pattern found in older readers with ASD of relative strength in word reading and weakness in reading comprehension (e.g., Brown et al, 2013; Nation et al, 2006) appears to be established early (Davidson & Weismer, 2014; Dynia et al, 2014; Dynia et al, 2017; Lanter et al, 2012). In the young children, it is print-related skills that are stronger and listening comprehension and vocabulary that are weaker, but the pattern appears to be similar.…”
Section: Discussionsupporting
confidence: 90%
“…Wide-spread difficulties with reading comprehension, often associated with average or better word reading accuracy, have been reported (Brown et al, 2013; Nation et al, 2006; O’Connor & Klein, 2004; Rickets, Jones, Happe, & Charman, 2013). An emerging body of research demonstrates that preschoolers with ASD show a pattern similar to that found in older readers with ASD: great heterogeneity, relatively stronger knowledge of print-related skills and relatively weaker oral language and phonological awareness skills (Davidson & Weismer, 2014; Dynia, Lawton, Logan, & Justice, 2014;Dynia, Brock, Justice, & Kaderavek, 2017; Lanter, Watson, Erickson, & Freeman, 2012; Westerveld et al, 2015) although Dynia et al (2014) found that the difference in phonological awareness disappeared when they controlled for oral language. As well, Dynia et al (2017) found that among young children with ASD, phonological awareness in preschool predicted later decoding achievement in kindergarten.…”
Section: Emergent Literacy and Children With Asdmentioning
confidence: 94%
“…Work on literacy skills should be included as part of the intervention program for any child with ASD. Blischak and Scholsser (2003); Koppenhaver and Erikson (2003) ;Lanter, Watson, Erickson, and Freeman, 2012;Lanter and Watson, 2008;and Mirenda (2003) provide suggestions for supporting literacy at various developmental levels in this population. If functional reading skills emerge, a written AAC system can be incorporated into the child's communication repertoire.…”
Section: Communication Assessment In Older Nonverbal Childrenmentioning
confidence: 99%